2022
DOI: 10.1002/smll.202200813
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Luminescence‐Based Theranostics for Real‐Time Monitoring and Simultaneously Launching Photodynamic Therapy of Bacterial Infections

Abstract: External light irradiation is usually required in bacterial infection theranostics; however, it is always accompanied by limited light penetration, imaging interference, and incomplete bacterial destruction. Herein, a feasible “image‐launching therapy” strategy is developed to integrate real‐time optical imaging and simultaneous photodynamic therapy (PDT) of bacterial infections into persistent luminescence (PL) nanoparticles (NPs). Mesoporous silica NPs are used as a substrate for in situ deposition of PL nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…2 Wound infection occurs after pathogenic bacteria (usually Staphylococcus aureus (S. aureus)) invade the damaged tissues, and these wounds provide a nourishing environment for the growth of microorganisms. 3 In general, clinical symptoms such as redness, suppuration, and tissue damage will greatly increase when the bacterial load in 1 g of tissue exceeds 10 5 colony forming units (CFU). 4 This in turn triggers an increase inflammatory oxidative stress, which then impedes the natural progression of healing and reduces the effectiveness of wound healing.…”
mentioning
confidence: 99%
“…2 Wound infection occurs after pathogenic bacteria (usually Staphylococcus aureus (S. aureus)) invade the damaged tissues, and these wounds provide a nourishing environment for the growth of microorganisms. 3 In general, clinical symptoms such as redness, suppuration, and tissue damage will greatly increase when the bacterial load in 1 g of tissue exceeds 10 5 colony forming units (CFU). 4 This in turn triggers an increase inflammatory oxidative stress, which then impedes the natural progression of healing and reduces the effectiveness of wound healing.…”
mentioning
confidence: 99%
“…13,37 Next-generation wound dressings that are capable of real-time monitoring, early diagnosis, and on-demand therapy have received a lot of attention to overcome the woundhealing process's ''black box'' status. [38][39][40] Injured tissue generates exudate, a fluid rich in proteins such as electrolytes, creatinine, fibrinogen, matrix metalloproteinases (MMPs) and c-reactive protein (CRP), and tumor necrosis factor-alpha (TNF-a). 41,42 Additionally, certain physical wound environment factors, such as temperature, pH, humidity, and exercise, influence wound healing.…”
Section: Physiological Data For Monitoring the Wound Statusmentioning
confidence: 99%
“…More significantly, IR 820-DAA displayed outstanding wound healing in MRSA-infected mouse, with negligible consequences at the given dose. [166] Interestingly, there has been more intelligent approaches whereby researchers are looking at nanoparticles such as upconversion nanoparticles (UCNPs) [98,179] and persistent-luminescence nanoparticles (PL-NPs) [180,181] and to serve as light sources to excite the photosensitizers in a cascade manner, that has been applied in wound healing animal models.…”
Section: Chronic Wound Infections and Skin Infectionsmentioning
confidence: 99%
“…Similarly, in vivo studies showed that mPL@PcÀ Cy NPs could inactivate S. aureus with an antibacterial rate of over 99.5 %, with a wound recovery of 61.3 %. [180]…”
Section: Chronic Wound Infections and Skin Infectionsmentioning
confidence: 99%
See 1 more Smart Citation